Create, innovate, and serve : a radical approach to children's and youth programming - Campana, Kathleen; Mills, J. Elizabeth; Hildreth, Susan (ALA Neal-Schuman, 2019)
"This book is intended to give a broad overview of this radical landscape for public libraries in which librarians are creating innovative, interactive, participatory programming for children and youth by examining seven critical domains that occur across programming as a whole in part I and by taking an in-depth look at the different types of programs that are offered to children and youth that exemplify one of more of these domains in part II"--